STRENGTHENING CHILDREN'S LITERACY AND CHARACTER AS A STRATEGIC STEP IN COMMUNITY EMPOWERMENT: PENGUATAN LITERASI DAN KARAKTER ANAK SEBAGAI LANGKAH STRATEGIS PEMBERDAYAAN MASYARAKAT - HASNAWATI; GUNAWAN; SYARIFUDDIN; DIAN RIANI SAID; NAIMAH PARONDA (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Strengthening children's literacy and character is a strategic effort that plays an important role in community empowerment. Literacy, which includes reading and writing skills, allows children to access information critically and wisely, improve understanding, and develop their potential. On the other hand, character education forms fundamental values such as honesty, responsibility, cooperation, and discipline, which are essential in building a resilient and ethical personality. Through strengthening literacy and character from an early age, children are prepared to become productive and competitive individuals, as well as become agents of positive change in society. This strengthening program not only has a direct impact on children, but also makes a significant contribution to improving the social and economic quality of the community as a whole. Thus, children's literacy and character are an important foundation in creating a prosperous, independent, and empowered society.